Predictive Factors And Long-Term Visual Outcomes After Anti-Vascular Endothelial Growth Factor Treatment Of Retinal Angiomatous Proliferation - Maruyama-Inoue M (Dove Medical Press, 2019)
Maiko Maruyama-Inoue, Shimpei Sato, Shin Yamane, Kazuaki Kadonosono Department of Ophthalmology, Yokohama City University Medical Center, Yokohama, JapanCorrespondence: Maiko Maruyama-InoueDepartment of Ophthalmology, Yokohama City University Medical Center, 4-57 Urafune-cho, Minami-ku, Yokohama, Kanagawa 232-0024, JapanTel +81 45 261 5656Fax +81 45 253 8490Email maicoo@urahp.yokohama-cu.ac.jpPurpose: To report the results of 9-year follow-up examinations and predictive factors for visual acuity outcome after intravitreal injection of anti-vascular endothelial growth factor (VEGF) agents to treat retinal angiomatous proliferation (RAP).Methods: We conducted a retrospective observational study of 85 treatment-naïve eyes in 61 patients (21 men, 40 women; age range, 70–95 years; mean age, 84.0 years) treated with intravitreal injections of anti-VEGF agents. All patients received three consecutive monthly injections as an induction treatment. During the maintenance phase, the patients received intravitreal injections as needed or fixed dosing. The primary outcome measures were best-corrected visual acuity (BCVA) during the follow-up period. Furthermore, we investigated potential predictive factors of improvement in visual acuity. The proportion of patients who developed specific complications were also analyzed.Results: The mean BCVA gradually decreased from 0.58 at baseline to 0.70 at 36 months (P = 0.146), 0.82 at 48 months (P = 0.004), and 0.92 at 108 months (P = 0.021). Improvement in visual acuity at the final visits was associated with baseline visual acuity and central foveal thickness. Massive subretinal hemorrhage, fibrotic scars, and macular atrophy developed in 4 (4.7%), 9 (10.6%), and 50 (56.8%) eyes, respectively, at the final visits, and were all significantly associated with final visual acuity (P = 0.013, P < 0.001, and P = 0.001, respectively).Conclusion: Long-term stabilization of vision in patients with RAP, regardless of treatment modality, was difficult to achieve by using intravitreal injections of anti-VEGF agents. Earlier detection and treatment are important to maintain visual acuity in patients with RAP.Keywords: ranibizumab, aflibercept, retinal angiomatous proliferation, age-related macular degeneration, intravitreal injection